THE ROLE AND IMPORTANCE OF ALISHER NAVOI'S MORAL VIEWS IN ENRICHING THE SPIRITUAL WORLD OF A PERSON - M.M. Allayarova (Western European Studies, 2024)
The article focuses on the interpretation of the moral views of Alisher Navoi, one of the great Eastern scholars who created the concept of the Perfect Man. The moral ideas in his works have still not lost their value, and today's young generation is very important in enriching the spiritual world of the individual, there is a need to use this heritage in the educational system, humanity, justice, patriotism, goodness, love, patriotism in it. , it is highlighted that ideas such as self-interest, humanity, and honesty are embedded in the spiritual life of our people and the people of the region. It has been analyzed that the study of Navoi's works is important in the fight against vices such as corruption, arrogance, bribery, theft, dishonesty, and betrayal of the rights of others, which are global problems of ethics.
Keywords: enrichment of the spiritual world; corruption; arrogance